Clinical characteristics and outcomes in biclonal gammopathies. Issue 5 (6th April 2016) - Mullikin, Trey C.; Rajkumar, S. Vincent; Dispenzieri, Angela; Buadi, Francis K.; Lacy, Martha Q.; Lin, Yi; Dingli, David; Go, Ronald S.; Hayman, Suzanne R.; Zeldenrust, Steven R.; Russell, Stephen J.; Lust, John A.; et al.
Abstract : A single monoclonal protein typically characterizes monoclonal gammopathies, but a small proportion may have more than one M protein identifiable. In the setting of symptomatic multiple myeloma (MM), the development of a new monoclonal protein following therapy is associated with better outcomes. As for the precursor conditions, monoclonal gammopathy undetermined significance (MGUS) and smoldering multiple myeloma (SMM), there is limited information on the impact of a second monoclonal protein on the disease course, including progression and response to treatment. The outcomes of patients with MGUS and SMM with more than one monoclonal protein, after identifying 539 patients with biclonal proteins on electrophoresis and/or immunofixation, were reported. About 22 of 393 patients with MGUS/biclonal gammopathy of undetermined significance (BGUS) progressed to SMM (6), MM (11), AL (3), or WM (2), and 5 of 16 patients with biclonal SMM progressed to MM. The rate of progression for BGUS was approximately 1% per year, which is similar to MGUS with one monoclonal protein. The median estimated time of progression of biclonal SMM was 2.6 years; similar to monoclonal SMM. For patients with biclonal MM, both M spikes responded to treatment and, upon relapse, the original dominant M protein remained dominant as the disease progressed. In conclusion, the presence of a second monoclonal protein does not appear to affect the progression of precursor states and suggests multiple monoclonal proteins do not clinically impact one another in the course of the disease. Am. J. Hematol. 91:473–475, 2016. © 2016 Wiley Periodicals, Inc.